“Colpitis en gestantes atendidas en el hospital provincial N° 2 Yarinacocha Pucallpa 1993 – 1994” - Ramírez Navarro, Lidmer (1995)
The colpitis constitutes frequent consultations a gynecological cause; a sexually transmitted disease, because this is the most common way of infection. (11, 30) To understand and treat the colpitis with good results, it is important to be familiar with the resident microflora in healthy vagina (34); since normally the female adult has large amount of bacilli of Döderlein that have as function convert the glycogen of them cells vaginal desquamated in acid lactic, acidifying the vagina and exerting a self-purging. (2, 13, 17) The colpitis is an infection of the mucous vulvar or vaginal with or without compromising urethra or cervix and is characterized by the following symptoms: abnormal vaginal discharge, dyspareunia, dysuria, pain, pruritus Vulvae, marked vaginal odor, among others (7). The infectious causes of vaginal discharge range from viruses to protozoa, including bacteria and fungi, i.e., by the complex and varied microflor...